2022
DOI: 10.1002/adfm.202113374
|View full text |Cite
|
Sign up to set email alerts
|

Underwater Directional and Continuous Manipulation of Gas Bubbles on Superaerophobic Magnetically Responsive Microcilia Array

Abstract: The manipulation of underwater bubbles is of great significance in scientific research and industrial applications since they are ubiquitous and inevitable in production and life, for example, in agriculture and industry processes. Unfortunately, in an aqueous environment, the bubbles are mainly dominated by buoyancy and move upward, which makes the manipulation of bubbles difficult. To this end, numerous materials have been designed to manipulate bubbles. However, almost all of the existing materials are base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 28 publications
(8 reference statements)
1
30
0
Order By: Relevance
“…In addition, Wang et al also made a flexible slippery track, which improved the flexibility and application fields of the slippery track and further accelerated the promotion of bubble control technology. Furthermore, some other external dynamics, such as magnetic response, have also been considered to improve the control stability of the bubbles. , We noticed that the existing methods of bubble transport either have limited controllability and transport distance, rely on buoyancy as the driving force, or need to introduce specific external magnetic field, all of which limit their practical application. To address this critical issue, it is necessary to redesign the surface structure so that it can not only improve the control of bubble transport but also be applicable to more driving scenarios.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…In addition, Wang et al also made a flexible slippery track, which improved the flexibility and application fields of the slippery track and further accelerated the promotion of bubble control technology. Furthermore, some other external dynamics, such as magnetic response, have also been considered to improve the control stability of the bubbles. , We noticed that the existing methods of bubble transport either have limited controllability and transport distance, rely on buoyancy as the driving force, or need to introduce specific external magnetic field, all of which limit their practical application. To address this critical issue, it is necessary to redesign the surface structure so that it can not only improve the control of bubble transport but also be applicable to more driving scenarios.…”
supporting
confidence: 93%
“…Many efforts have been made in this field, but challenges still remain. , Zhang et al found that gas can flow, as well as merge and split precisely, in channels of elastic liquid-infused material. Therefore, it seems to be a feasible solution to control the growth and transport of bubbles with microchannels on the surface. , Moreover, a hydrophobic surface with a topological structure has been shown to power the slipping of bubbles, which may improve the control of bubbles. ,, For instance, Yu et al designed a superhydrophobic helix, and they found that the attached bubble can transport alongside it under the action of buoyancy during the rotation of the helix. In addition, Wang et al also made a flexible slippery track, which improved the flexibility and application fields of the slippery track and further accelerated the promotion of bubble control technology.…”
mentioning
confidence: 99%
“…A representative example is an aquatic spider ,, that uses fibered superhydrophobic cuticles to capture bubbles and sustain a stable air layer, which inspires many underwater applications, such as selective electrocatalysts . By taking advantage of special geometry such as conical or wedged-shaped structures or applying external driving forces, bubbles can be directionally transported and collected in the preferred location to replenish the air layer underwater. Active bubble generation by chemical reactions can also be harnessed to sustain a stable air layer within structures underwater. , …”
Section: Air-infused Liquid-repellent Surfacesmentioning
confidence: 99%
“…In various application sceneries, such as environmental, agricultural, chemical, and biological engineering, bubbles are ubiquitous in aqueous media 1 . Substantial efforts have been made to investigate the manipulation of underwater bubbles in the past decades 2–4 . In comparison with larger bubbles, tiny bubbles possess numerous advantages, such as large special surface area, additional Laplace pressure, 4 small rising velocities, and high mass transfer efficiency 5 .…”
Section: Introductionmentioning
confidence: 99%